Ответ:
2) х = [-1;1]
3)х= (-бесконечность; -103)
Объяснение:
2) -2 <= 3х +1<=4</p>
Что бы решить двойное неравенство, следует разделить его на два неравенства.
![3x + 1 \geqslant - 2 \\ 3 \times + 1 \leqslant 4 \\ x \geqslant - 1 \\ x \leqslant 1 3x + 1 \geqslant - 2 \\ 3 \times + 1 \leqslant 4 \\ x \geqslant - 1 \\ x \leqslant 1](https://tex.z-dn.net/?f=3x%20%2B%201%20%5Cgeqslant%20%20-%202%20%5C%5C%203%20%5Ctimes%20%20%2B%201%20%5Cleqslant%204%20%5C%5C%20x%20%5Cgeqslant%20%20-%201%20%5C%5C%20x%20%5Cleqslant%201)
Ответ: х = [-1;1]
3)
\frac{x + 1}{3} + 7 \\ 3(x - 1) - 12 > 4(x + 1) + 84 \\ 3x - 3 - 12 > 4x + 4 + 84 \\ 3x - 15 > 4x + 88 \\ 3x - 4x > 88 + 15 \\ - x > 103" alt=" \frac{x - 1}{4} - 1 > \frac{x + 1}{3} + 7 \\ 3(x - 1) - 12 > 4(x + 1) + 84 \\ 3x - 3 - 12 > 4x + 4 + 84 \\ 3x - 15 > 4x + 88 \\ 3x - 4x > 88 + 15 \\ - x > 103" align="absmiddle" class="latex-formula">
ответ: х= (-
![\infty \infty](https://tex.z-dn.net/?f=%20%5Cinfty%20)
; -103)